Effects of Structured Health Education and Multimodal Intervention on Behavioural and Clinical Outcomes in Type 2 Diabetes Mellitus: A Quasi-Experimental Study - Sarmalina Simamora; Tedi Tedi; Sonlimar Mangunsong (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic disease commonly found in individuals over the age of 40 and ranks among the top three diseases suffered by participants of the National Health Insurance (JKN) program. The management of T2DM often involves the long-term use of medications, both oral and injectable, which may extend throughout the patient's lifetime. This condition can worsen in the presence of complications. However, T2DM patients can maintain a good quality of life and reduce the risk of macrovascular and microvascular complications if their blood sugar, blood pressure, and cholesterol levels are well-controlled. Effective management requires more than just medication; proper dietary regulation and sufficient physical activity are also crucial. This study aims to enhance the understanding and behaviors of T2DM patients so that they can achieve optimal clinical parameters and reduce the risk of complications. Method: The research employs a quasi-experimental pre–post design was applied involving 20 adults with T2DM divided into treatment and control groups. The intervention consisted of face-to-face education, booklets, and exercise videos. Behavioral and clinical outcomes were assessed before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test and paired t-test based on data distribution. Result: The results showed significant improvements in understanding and behavior related to medication use, meal practices, and physical activity in the treatment group based on the Wilcoxon test (p < 0.05). However, no significant improvement was observed in dietary-management understanding. Conclusion: Structured health education combined with multimodal intervention demonstrated significant improvements in behavioral and selected clinical outcomes among patients with type 2 diabetes mellitus compared with the control group.